El sentido de la distinción entre las perspectivas de primera y tercera persona - José Sanguineti, Juan (Sapientia, 2017)
The distinction between the first and third-person perspectives was proposed in the philosophy of mind as a reaction against the naturalistic closure within the limits of empirical objectivity. The first-person perspective is irreducible and is present, at least implicitly, not only in psychology and neuroscience, but even in every science, since knowledge presupposes the knower. The distinction cannot be limited to epistemology, but should rather be ontologically explained, in order to avoid the danger of eliminating the subject and consequently to view the Self as fictitious (Metzinger). Baker’s realistic ontology of the first-person perspective (constitutionalism) is assessed as insufficient and prone to drastic dualism. The Thomistic (hylemorphic) view is able to provide a realistic account of the Self and its relation with the human body. In the classical philosophical tradition the distinction between subjective knowledge and objects known is not problematic. The problem was rather to give an account of the intellectual experience of individual things.